Highly efficient methanol oxidation reaction on durable Co9S8 @N, S-doped CNT catalyst for methanol fuel cell applications. (15th January 2022) - Ashok, Anchu; Kumar, Anand; Yuda, Afdhal; Al Ashraf, Abdullah
Abstract: The implementation of direct methanol fuel cells is seen as a reliable factor in the future energy mix. Efficient energy conversion from methanol requires an active and durable catalyst to drive the anodic methanol oxidation reaction (MOR) in direct methanol fuel cells. As an alternative to high cost noble metals, cobalt-based electrocatalysts are considered potential replacements that meet the high activity and long-term stability for MOR. Herein, we report the preparation of hierarchical Co9 S8 nanowires trapped in N-doped carbon nanotubes (N, S–Co@CNT) derived from melamine showing high activity for MOR in alkaline medium. In order to identify the main active sites, we synthesized cobalt particles embedded in carbon structures in absence of a sulphur source (Co@CNT) and evaluated its performance for MOR. The material characterization shows that adding sulphur during pyrolysis enhances the surface area, pore size and lattice defect. In addition, the morphology changes from hemi-spherical particles to nanowires, that significantly improves the electrochemical properties. The current density of N, S–Co@CNT is exceptionally higher (5.5 times) and the onset potential of MOR is shifted to lower potential when compared to Co@CNT. The enhanced activity, durability and stability of N, S–Co@CNT is ascribed to the unique hierarchical structure and surface properties. Highlights: Cobalt sulfide nanowires were synthesized with MWCNT using melamine pyrolysis. Presence of sulphur in Co markedly improved the methanol electrocatalytic activity. Different structures of carbon, MWCNT and bamboo CNT, formed during the pyrolysis. The current density of N, S–Co@CNT was 5.5 times higher than Co@CNT for MOR.